Appropriate Treatment for Bloodstream Infections Due to Carbapenem-Resistant Klebsiella pneumoniae and Escherichia coli: A Nationwide Multicenter Study in Taiwan. (17th December 2018) - Lin, Yi-Tsung; Su, Chin-Fang; Chuang, Chien; Lin, Jung-Chung; Lu, Po-Liang; Huang, Ching-Tai; Wang, Jann-Tay; Chuang, Yin-Ching; Siu, L Kristopher; Fung, Chang-Phone
Abstract: Background: In a multicenter study from Taiwan, we aimed to investigate the outcome of patients who received different antimicrobial therapy in carbapenem-resistant Enterobacteriaceae bloodstream infections and proposed a new definition for tigecycline use. Methods: Patients from 16 hospitals in Taiwan who received appropriate therapy for bloodstream infections due to carbapenem-resistant Klebsiella pneumoniae and Escherichia coli were enrolled in the study between January 2012 and June 2015. We used a cox proportional regression model for multivariate analysis to identify independent risk factors of 14-day mortality. Tigecycline was defined as appropriate when the isolates had a minimum inhibitory concentration (MIC) ≤0.5 mg/L, and we investigated whether tigecycline was associated with mortality among patients with monotherapy. Results: Sixty-four cases with carbapenem-resistant K pneumoniae (n = 50) and E coli (n = 14) bloodstream infections were analyzed. Of the 64 isolates, 17 (26.6%) had genes that encoded carbapenemases. The 14-day mortality of these cases was 31.3%. In the multivariate analysis, Charlson Comorbidity Index (hazard ratio [HR], 1.21; 95% confidence interval [CI], 1.03–1.42; P = .022) and colistin monotherapy (HR, 5.57; 95% CI, 2.13–14.61; P < .001) were independently associated with 14-day mortality. Among the 55 patients with monotherapy, the 14-day mortality was 30.9% (n = 17). Tigecycline use was not associated with mortality in the multivariate analysis. Conclusions: Tigecycline monotherapy was a choice if the strains exhibited MIC ≤0.5 mg/L, and colistin monotherapy was not suitable. Our findings can initiate additional clinical studies regarding the efficacy of tigecycline in carbapenem-resistant Enterobacteriaceae infections.